A New Method to Measure Portal Venous and Hepatic Arterial Blood Flow Patients Intraoperatively. Issue 4 (1996) - Jakab, F.; Ráth, Z.; Schmal, F.; Nagy, P.; Faller, J.
Abstract : The intraoperative measurement of the afferent circulation of the liver, namely the hepatic artery flow and portal venous flow was carried out upon 14 anesthetized patients having carcinoma in the splanchnic area, mainly in the head of the pancreas by means of transit time ultrasonic volume flowmeter. The hepatic artery flow, portal venous flow and total hepatic flow were 0.377±0.10; 0.614±0.21; 0.992±0.276 l/min respectively. The ratio of hepatic arterical flow to portal venous flow was 0.66±0.259 There was a sharp, significant increase in hepatic arterial flow (29.8±6.1%, p<0, 01) after the temporary occlusion of the portal vein, while the temporary occlusion of hepatic artery did not have any significant effect on portal venous circulation. The interaction between hepatic arterial flow and portal venous flow is a much disputed question, but according to the presented data here, it is unquestionable, that the decrease of portal venous flow immediately results a significant increase in hepatic artery circulation.